Graphitic carbon derived from one-step carbonization of pre-pelleted oil palm frond biomass for supercapacitor applications: Energy density enhancement in redox additive electrolytes - Ullah, Mohammad; Rasidi, Roslan; Jose, Rajan; Izan Izwan, Misnon (Elsevier Ltd, 2025)
The typical methods of carbon activation (i.e., chemical or physical) are costly in terms of time and cost and use large quantities of detrimental chemicals, such as KOH, NaOH, and ZnCl2, as activation agents. This work proposed a new synthetic protocol utilizing pellet-form graphitic carbon (PGC) derived from oil palm frond biomass without activating agents. The PGC was characterized using several characterization tools (XRD, FE-SEM, XPS, FTIR, BET, and Raman Spectroscopy), and the electrochemical properties were evaluated by varying the electrolytes (H2SO4, KOH, and Na2SO4) to compare the capacitive performance in different electrolyte. The PGC has an optimal edge fraction of 0.279, an average number of layer planes in a crystallite of 2.748, high carbon content (∼95 %), a pore size distribution of 2.33 nm, and an ID/IG ratio of 0.82. The PGC has an optimum specific capacitance (CS) of 334 F g−1 in 1 M H2SO4 at a current density of 1 A g−1. The fabricated symmetric supercapacitor (SSC) device delivered an energy density (ED) of 18.86 Wh kg−1 at a power density (PD) of 1386 W kg−1. The PGC was further investigated using three redox additives in 1 M H2SO4 electrolyte. The hydroquinone additive (HQ/H2SO4) exhibited the highest CS ∼ 658 F g−1 (∼1053 C g−1), whereas ammonium monovanadate (AM/H2SO4) with CS ∼ 598 F g−1 (∼957 C g−1), and potassium ferrocyanide (PF/H2SO4) with CS ∼ 448 F g−1 (717 C g−1). The SSC achieved a maximum ED and PD of 36 Wh kg−1 and 2400 W kg−1, respectively. The SSC exhibits a capacity retention of 91 % after undergoing 10,000 cycles.